An efficient approach for the synthesis, characterization, and antifungal studies of chlorantraniliprole carboxamide derivatives - Tyagi, Vikas Kumar; Kumar, Ajay; Bhatt, Bhawana; Tewari, Sanjana (Revista Brasileira de Engenharia de Biossistemas, 2026)
The structural modification of established agrochemical scaffolds remains a powerful strategy for developing next-generation fungicidal agents with enhanced efficacy and safety. In this study, an efficient and mild peptide-coupling approach was developed for the synthesis of a new series of chlorantraniliprole (CTPR)-based carboxamide derivatives (1a–1j). The protocol employs a 1-hydroxybenzotriazole/1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide (HOBt/EDC·HCl)-mediated amide bond formation between 3-bromo-1-(3-chloropyridin-2-yl)-1H-pyrazole-5-carboxylic acid and a diverse set of aromatic, aliphatic, and cyclic amines under ambient conditions, affording the target compounds in good to excellent yields (65.33–93.68%). The method is operationally simple, reproducible, and avoids harsh reagents or elevated temperatures. Structural elucidation of the synthesized compounds was accomplished using 1H NMR, FTIR, and ESI–MS analyses. The antifungal potential of all derivatives was evaluated in vitro against five major phytopathogenic fungi, such as Alternaria, Fusarium, Rhizoctonia, Helminthosporium, and Aspergillus, using the poisoned food technique, with hexaconazole as the reference fungicide. The biological results revealed a strong dependence of antifungal activity on amine substitution. Compounds bearing short-chain aliphatic or heterocyclic amines exhibited markedly superior activity compared to aromatic analogues. In particular, derivatives 1c, 1h, 1i, and 1j demonstrated broad-spectrum antifungal efficacy, frequently outperforming hexaconazole and, in some cases, achieving complete growth inhibition at higher concentrations. Structure-activity relationship (SAR) analysis indicated that smaller open-chain amines and polar heterocyclic substituents significantly enhance antifungal performance, likely due to improved hydrophobic and hydrogen-bonding interactions with fungal targets. Overall, this work presents a practical synthetic route to CTPR-based carboxamides and identifies several promising lead compounds for the development of novel, effective, and potentially eco-friendly fungicidal agents.